Can natural language be utilized in the learning of programming fundamentals? - Oliveira, Osvaldo Luiz; Monteiro, Ana Maria; Trevisan Roman, Norton (2013 IEEE Frontiers in Education Conference (FIE), 2013)
The complexity and importance of learning programming fundamentals (i.e., sequences of sentences that express actions, conditions, and repetitions in computing) for undergraduate students has motivated the development of an intense educational research area. One frequently studied problem is the difficulty in the learning of traditional context-free grammars which are present, for example, in programming languages such as Pascal and C. This study experimentally investigates the use of natural language in the learning of programming fundamentals by two groups of undergraduate students without prior knowledge of programming and compares its use with that of a traditional grammar language. Results suggest that the use of natural language is a good alternative, despite the small differences, to the use of traditional programming languages defined by context-free grammars. This alternative is attractive and promising because the student does not need to learn a formal grammar to learn the fundamentals of programming.